POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG NOMOR 13 TAHUN 2022 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DALAM PERSPEKTIF ASAS PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Apri Wulandari Panjaitan; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The formation of laws and regulations must based on the principles of forming good laws andregulations, including: Clarity of Institutional Purposes or appropriate forming officials Conformitybetween types, hierarchies, and content material. The formation of Law Number 13 of 2022 is a follow-upto the Constitutional Court Decision Number 91/PUU-XVIII/2020 as a basic order to regulate theOmnibus method and meaningful participation.This type of normative juridical research, because this research is carried out by examining secondarydata and approaches to laws, this normative research examines the applicable regulations and relatesthem to legal politics in the formation of laws and regulations. to achieve the ideal criteria in amendingLaw Number 13 of 2022 Second Amendment to Law Number 12 of 2011 concerning Formation ofLegislation. The data sources used are primary data, secondary data, tertiary data, the data collectiontechnique in this study is normative juridical, the data used is library research.The results of this study examine and analyze the urgency of the state in the Formation of Law Number13 of 2022 where the law has canceled 6 (six) principles out of 7 (seven) principles for the formation oflaws and regulations and assesses the Ideal criteria in accordance with the aspired law (iusconstituendum) in the Amendment to Law Number 13 of 2022 Second Amendment to Law Number 12 of2011 concerning the Formation of Laws and Regulations based on the Indonesian constitutional system,namely the theory of laws adopted by the Indonesian legal system.Keyword: Law, Principles Of Formation Of Legislation, Legal Politics.